PENGARUH HIDROGEN TERHADAP KEKUATAN TARIK KELONGSONG BAHAN BAKAR NUKLIR BERBASIS PADUAN ZIRKONIUM - Sigit, Rohmad; Al Afghani, Fajar; Setiawan, Jan; Sungkono (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
During reactor operation, zircaloy-4 (Zr-4) as fuel cladding is under an environment that can potentially cause mechanical failure, especially by the effect of cladding-hydrogen interaction. Hydrogen would diffuse and precipitate to form brittle hydrides when the solubility limit is surpassed. In this experiment, ring tensile test method was used to examine the effect of hydrides existence on tensile strength of Zr-4 cladding. The Zr-4 sample was annealed at 500 °C and 600 °C for an hour in vacuum condition and followed by hydriding with a pressure up to 1000 mbar with 3 hours holding time and slow cooling. According to ideal gas equation, hydrogen content in Zr-4 reaches about 674 ppm and 1215 ppm at hydriding temperature of 500 °C and 600 °C respectively. Microstructure observation shows that hydrides precipitate was formed at grain boundaries. The hydrides were found to be longer and thicker at higher hydriding temperature. As the hydrogen content increases, the ring tensile test shows increasing stress at 4.4 %, decreasing strain at 2.1 % and increasing microhardness level at 13 %. This result confirms that the existence of hydrides precipitates in cladding has an effect of increasing the tensile strength and decreasing the ductility obviously.